Assessment of the possibility of using the digital platform of the Federal Tax Service of Russia in determining the tax burden of the organization - A. V. Zakharova; L. S. Samodelko; E. A. Kirova (Вестник университета)
The article presents the results of calculating the tax burden on the example of a specific organization, which are based on accounting (financial) and tax reporting data, which are digital data of the information and digital platform of the Federal Tax Service of Russia, as well as the results of identifying the socio-environmental factor in order to identify its impact on the tax burden. The purpose of the research paper is to assess the tax burden of organizations and identify the socio-environmental factor on the basis of the information platform of the Federal Tax Service of the Russian Federation. On the basis of the analysis and synthesis, the authors summarized the results of the taxation of organizations, taking into account the digital technologies of the civil service, and also formulated conclusions about the further development of the sphere of digital services in the field of taxation, which is necessary for assessing the tax burden as a significant resulting indicator of the activities of organizations.